Separation of concerns in hybrid component and agent systems. (11th February 2011) - Dragone, Mauro; Jordan, Howell; Lillis, David; Collier, Rem W.
This paper discusses the Socially Situated Agent Architecture (SoSAA) – a complete construction methodology that leverages existing well-established research and associated methodologies and frameworks in both the agent-oriented and component-based software engineering domains. As a software framework, SoSAA is intended to serve as a foundation on which to build agent-based applications by promoting separation of concerns in the development of open, heterogeneous, adaptive and distributed systems. The paper highlights concerns typically addressed in the development of distributed systems, such as adaptation, concurrency and fault-tolerance. It analyses how a hybrid agent/component integration approach can improve the separation of these concerns by leveraging modularity constructs already available in agent and component systems. Finally, it provides a first evaluation of the framework's application by applying well-known metrics to a distributed information retrieval case study, and by discussing how these results can be projected to a typical multi-agent application developed with this hybrid approach.